\[\boxed{\text{355\ (355).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[y = - x^{2} + 9x + 9\]
\[1)\ x = y\]
\[- x^{2} + 9x + 9 = x\]
\[x^{2} - 8x - 9 = 0\]
\[x_{1} + x_{2} = 8,\ \ x_{1}x_{2} = - 9\]
\[x_{1} = 9,\ \ x_{2} = - 1.\]
\[Ответ:(9;9),\ \ \ ( - 1; - 1).\]
\[2)\ x + y = 25,\ \ y = 25 - x\]
\[- x^{2} + 9x + 9 = 25 - x\]
\[x^{2} - 10x + 16 = 0\]
\[x_{1} + x_{2} = 10,\ \ x_{1} = 8\]
\[x_{1}x_{2} = 16,\ \ x_{2} = 2.\]
\[x = 8,\ \ y = 17;\]
\[x = 2,\ \ y = 23.\]
\[Ответ:(8;17),\ \ \ (2;23).\]
\[\boxed{\text{355.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ y = 9x - 4 - возрастающая,\ \]
\[так\ как\ k = 9,\ k > 0.\]
\[2)\ y = - 4x + 10 - убывающая,\ \]
\[так\ как\ k = - 4,\ k < 0.\]
\[3)\ y = 12 - 3x - убывающая,\ \]
\[так\ как\ k = - 3,\ k < 0.\]
\[4)\ y = - x - убывающая,\ \]
\[так\ как\ k < 0.\]
\[5)\ y = \frac{1}{6}x - возрастающая,\ \]
\[так\ как\ k > 0.\]
\[6)\ y = 1 - 0,3x - убывающая,\ \]
\[так\ как\ k < 0.\ \]